2013
DOI: 10.1371/journal.pone.0078157
|View full text |Cite
|
Sign up to set email alerts
|

Serglycin Is Implicated in the Promotion of Aggressive Phenotype of Breast Cancer Cells

Abstract: Serglycin is a proteoglycan expressed by some malignant cells. It promotes metastasis and protects some tumor cells from complement system attack. In the present study, we show for the first time the in situ expression of serglycin by breast cancer cells by immunohistochemistry in patients’ material. Moreover, we demonstrate high expression and constitutive secretion of serglycin in the aggressive MDA-MB-231 breast cancer cell line. Serglycin exhibited a strong cytoplasmic staining in these cells, observable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 54 publications
(85 reference statements)
7
80
0
4
Order By: Relevance
“…Recently it has been shown that serglycin promotes breast cancer cell anchorage-independent growth, migration and invasion of breast cancer cells and these properties are dependent on the expression and secretion of glycanated serglycin bearing CS chains [33]. …”
Section: Extracellular Matrices In Breast Cancer: Focus On the Promentioning
confidence: 99%
See 4 more Smart Citations
“…Recently it has been shown that serglycin promotes breast cancer cell anchorage-independent growth, migration and invasion of breast cancer cells and these properties are dependent on the expression and secretion of glycanated serglycin bearing CS chains [33]. …”
Section: Extracellular Matrices In Breast Cancer: Focus On the Promentioning
confidence: 99%
“…Serglycin is highly expressed in breast cancer tissues and cell lines [33]. The mRNA levels of serglycin are markedly up-regulated in aggressive breast cancer cells clustered into Basal B subgroup, which exhibit an EMT gene signature and resemble breast cancer stem cells being CD44 high CD24 low [33].…”
Section: Serglycin: An Inflammatory Proteoglycan That Is Involved mentioning
confidence: 99%
See 3 more Smart Citations